(untitled) (Research, Society and Development, 2021)
Objective: to assess anxiety and self-esteem in chronic kidney patients undergoing hemodialysis treatment. Method: Descriptive-analytical, cross-sectional, quantitative study developed with 108 people with chronic renal failure undergoing hemodialysis treatment at a general hospital in a city in the south of Minas Gerais, Brazil. Data were collected through interviews, using a characterization instrument , the Rosenberg Self-Esteem Scale and the Hospital Anxiety and Depression Scale. For data analysis, descriptive statistics, Pearson’s chi-square test, Fisher’s exact test, odds ratio and logistic regression were used. Results: Some participants had anxiety (25.9%) and most of them had a medium level of self-esteem (52.8%). There was a significant association between the variables length of hemodialysis treatment, important events in life, monthly family income and type of access to hemodialysis with anxiety (p<0.05). It was also found that monthly family income and duration of hemodialysis treatment were significantly associated with the measure of self-esteem (p<0.05). The anxiety of chronic kidney patients undergoing hemodialysis treatment was significantly associated with self-esteem (p<0.05). Conclusion: Some patients had anxiety and most of them altered self-esteem, and patients who had anxiety were more likely to have medium/low self-esteem. Thus, there is a need for nursing strategies that provide an improvement in these levels, contributing positively to the quality of life of these patients.